An assessment tool for healthcare waste management in Brazilian municipalities during the COVID-19 pandemic - Moraes, Flávia Tuane Ferreira (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
The COVID-19 pandemic has put healthcare waste management (HCWM) systems under pressure worldwide. In Brazil, where municipalities routinely experience challenges in ensuring suitable disposal of healthcare waste (HCW), the pandemic has made this even more challenging. Therefore, the creation of tools and methods to help in municipal HCWM during the COVID-19 pandemic is of utmost importance. This article presents the development of a tool to evaluate HCWM in Brazilian municipalities during the pandemic. Following guidelines of health agencies, 56 indicators and 18 criteria were selected to create a tool called the municipal healthcare waste management assessment index (iMHWaste). These indicators and criteria were divided into operational, environmental, political-economic, educational and social groups. Each group considers essential aspects for sustainable management, safety and reduced spread of coronavirus. The analytic hierarchy process was used to assign the weights attributed to the groups and criteria. The indicators can be measured according to a standardized rating scale proposed for each one. These elements were aggregated with a weighted linear combination, into an equation that allows the calculation of the iMHWaste. The index is rated on a scale of 0-1. The index was applied in a Brazilian municipality considering a pre-pandemic HCWM. With the identification of the municipality's management weaknesses, it was possible to identify the main actions that should be prioritized in the transition from traditional HCWM during the pandemic